Causal Factor Analysis of Fatal Accidents in Johor Construction Industries Based on Korean Occupational Safety and Health Agency Classification - Syed Zakaria, Sharifah Nurul Afiqa; Abas, Nor Haslinda; Mohd Ta'at, Nurul Hasanah; Abas, Nor Ain; Abdul Ghani, Abdul Halim (International Journal of Integrated Engineering, 2023)
Construction work is widely regarded as an accident-prone industry, with hazards and dangers that have the potential to cause numerous injuries or even deaths. Thus, building an accident-free construction environment constitutes one of the core concerns of the industry in achieving sustainable construction. Occupational fatal accidents statistics investigated by Department of Occupational Safety and Health indicate that the construction industry recorded the highest number of deaths from 2015 to 2021. In order to determine the correlation between unsafe acts (UAs) and unsafe conditions (UCs) for accident causes, this study analyses the causes of fatal accidents at Johor construction sites using the categorization developed by the Korean Occupational Safety and Health Agency. The data was analysed using the SPSS software application, with a chi-square and lambda test to determine the significant combinations by determining the relationship between UAs and UCs. Other than that, this study explored and improved the understanding of UAs and UCs of accidents at construction sites. This will be more helpful for preventing accidents at construction sites. A study in a larger scope and using more detailed data would be helpful in future studies.